Implementing a data warehouse : a methodology that worked - Ullrey, Bruce Russell (United States of America: Authorhouse, 2007)
The purpose of this book is to document the methodology and chronology of work activity used to successfully implement a data warehouse. Each step of the methodology is presented in the book, often using actual working documents as examples. The book contains lessons learned (both good and bad) as well as measures of success for each step. Again, the purpose of this book is to provide actual examples of processes, work papers, technical documentation, pitfalls and measures of success that led to a successful working data warehouse. This is not "The BEST and ONLY Book" for implementing a data warehouse and associated BI, but if a reader wants to see a methodology that worked - this book will provide that view
Includes bibliographical references
Audiencia general
Practice the due diligence our profession -- Build busines models -- Define business requirements based upon the busines models -- Identify data sources based upon defined requirement -- Select a data warehouse toolset based upon defined requirements -- Build the data warehouse -- Build the data marts -- Build the initial OLAP templates -- Train the data warehouse user -- Deploy the data warehouse -- Begin data warehouse support
Keywords: Programación (computadores electrónicos) -- Administración; Almacenamiento de datos